Effect of cattle breeding on habitat use of Pampas deer Ozotoceros bezoarticus celer in semiarid grasslands of San Luis, Argentina - Merino, Mariano Lisandro (2011)
The largest population of the Argentinean Pampas deer Ozotoceros bezoarticus celer is found in the semiarid grasslands of the San Luis province. Despite relatively high deer numbers in the region, there has been concern that expansion of farming practices could displace the species. Since the 1990’s, cattle breeding has intensified especially as a result of the replacement of natural grassland with South African digit grass (Digitaria eriantha) and African lovegrass (Eragrostis curvula). In this study, we studied how deer in “El Centenario” ranch used available habitat types, especially to assess whether it preferentially used natural over exotic pastures. We employed 8 fixed line transects to record deer numbers and habitat use during the dry season, early rainy and late rainy seasons. We estimated a mean population size of 731 ± 121 individuals, a density of 1.95 ± 0.25 deer/km2. Our results also showed that deer did not appear to select natural pastures over exotic ones, though D. eriantha grasslands with cattle were used less during the late rainy season. Grazed pastures with D. eriantha without cattle were used significantly more during all time periods. Our results therefore suggest that Pampas deer are not shifted by exotic pastures but we caution that it is important to manage these habitats sustainably (e.g. cattle load adjusted to grassland nutritional supply, rotational crops with parcel rest period), to ensure the conservation of the species within agricultural areas.